Respostas

A melhor resposta!
  • Usuário do Brainly
2013-11-23T16:24:02-02:00
Dados:
P.A crescente (a1, a2, a3, a4, a5, a6) ; > 0 (crescente)
(a1) + (a3) + (a5) = 27
(a2) + (a4) + (a6) = 36
a3 = ?

então:
(a1) + (a1 + 2r) + (a1 + 4r) = 27
(a1 + r) + (a1 + 3r) + (a1 + 5r) = 36
----------------------------------------------------
3 a1 + 6r = 27
3 a1 + 9r = 36
-------------------------------
3 a1 + 6r = 27 .(-1) (I)
3 a1 + 9r = 36 (II)
--------------------------------
- 3 a1 - 6r = - 27
3 a1 + 9r = 36
---------------------------------
3r = 9
r =  \frac{9}{3}
r = 3

--------------------------------------
encontrar a1:
3 a1 + 9r = 36 (II)
3 a1+ 9*3 = 36
3 a1 + 27 = 36
3 a1 = 36 - 27
3 a1 = 9
a1 =  \frac{9}{3}
a1 = 3
------------------------
encontrar a3:
a3 = a1 + 2r
a3 = 3 + 2*3
a3 = 3 + 6
a3 = 9

resposta:
a3 = 9



5 5 5